Pathology-related changes in cardiac energy metabolites, inflammatory response and reperfusion injury following cardioplegic arrest in patients undergoing open-heart surgery - Skeffington, Katie L.; Moscarelli, Marco; Abdul-Ghani, Safa; Fiorentino, Francesca; Emanueli, Costanza; Reeves, Barnaby C.; Punjabi, Prakash P.; Angelini, Gianni D.; Suleiman, M-Saadeh (Frontiers in Cardiovascular Medicine, 2022)
Introduction Changes in cardiac metabolites in adult patients undergoing open-heart surgery using ischemic cardioplegic arrest have largely been reported for non-ventricular tissue or diseased left ventricular tissue, with few studies attempting to assess such changes in both ventricular chambers. It is also unknown whether such changes are altered in different pathologies or linked to the degree of reperfusion injury and inflammatory response. The aim of the present work was to address these issues by monitoring myocardial metabolites in both ventricles and to establish whether these changes are linked to reperfusion injury and inflammatory/stress response in patients undergoing surgery using cold blood cardioplegia for either coronary artery bypass graft (CABG, n=25) or aortic valve replacement (AVR, n=16). Methods Ventricular biopsies from both left (LV) and right (RV) ventricles were collected before ischemic cardioplegic arrest and 20 mins after reperfusion. The biopsies were processed for measuring selected metabolites (adenine nucleotides, purines, and amino acids) using HPLC. Blood markers of cardiac injury (Troponin I, cTnI), inflammation (IL- 6, IL-8, Il-10 and TNFα, measured using Multiplex) and oxidative stress (Myeloperoxidase, MPO) were measured pre- and up to 72 hours post-operatively. Results The CABG group had a significantly shorter ischemic cardioplegic arrest time (38.6 ± 2.3min) compared to AVR group (63.0 ± 4.9min, p=2x10-6). Cardiac injury (cTnI release) was similar for both CABG and AVR groups. The inflammatory markers IL-6 and Il-8 were significantly higher in CABG patients compared to AVR patients. Metabolic markers of cardiac ischemic stress were relatively and significantly more altered in the LV of CABG patients. Comparing diabetic and non-diabetic CABG patients shows that only the RV of diabetic patients sustained major ischemic stress during reperfusion and that diabetic patients had a significantly higher inflammatory response. Discussion CABG patients sustain relatively more ischemic stress, systemic inflammatory response and similar injury and oxidative stress compared to AVR patients despite having significantly shorter cross-clamp time. The higher inflammatory response in CABG patients appears to be at least partly driven by a higher incidence of diabetes amongst CABG patients. In addition to pathology, the use of cold blood cardioplegic arrest may underlie these differences.